Strategic Formulation in Islamic Higher Education: A Case Study of IAIN Ponorogo Based on Hunger and Wheelen's Model - Effendi, Mukhlison (LP. Ma'arif Janggan Magetan, 2025)
The institutional transformation from the State Islamic College (STAIN) to the State Islamic Institute (IAIN) Ponorogo signifies not only a successful elevation in institutional status but also presents a challenge to continually enhance quality and quantity in the areas of education, research, community service, collaboration, and infrastructure. Based on the theory of strategy formulation of Hunger and Wheelen, this study aims to analyze the process of strategy formulation at IAIN Ponorogo. A qualitative approach was employed using a literature study method. The research locus is IAIN Ponorogo, with the Strategic Plan (Renstra) document serving as the primary data source. Key informants include structural officials involved in the preparation of the strategic plan. Data collection techniques involved document analysis and interviews, while data analysis was carried out through content analysis. The findings indicate that the formulation of the vision, mission, goals, objectives, and policy direction at IAIN Ponorogo aligns with the strategic formulation stages outlined by Hunger and Wheelen. This study contributes theoretically to the field of strategic management in Islamic higher education and provides practical implications for future institutional policy development.